RELATIONSHIP OF AUGMENTED REALITY MARKETING AND PERCEIVED PRICE ON CONSUMER PURCHASE INTENTION WITH MEDIATING ROLE OF BRAND IMAGE OF SHOPEE MALAYSIA - Tanah, Peter Kenny; Choo, Dennis, Ying Hoe (INTI International University, 2022)
There were contradictory findings where augmented reality brings enjoyable and playful elements to marketing but not necessary an effective tool for brand interaction and further investigation was required to minimize the gap. In contrast price was considered significant when judging the overall benefits when buying products in consumer's decision-making process. The research attempt to review the effectiveness of Augmented reality technology as an innovative approach to market products and services and the impact of price in online shopping. To investigate the effects of augmented reality marketing on consumer purchase intention; to investigate the effects of perceived price on consumer purchase intention and to investigate the interaction effects of brand image on augmented reality marketing and perceived price towards consumer purchase intention. The study was conducted in Malaysia using online survey with a convenient sample of 250 Shopee respondents for a period of 4 weeks in Mid 2021– a pilot study was conducted prior the actual survey to test the validity and reliability of the research instrument. The data collection was obtained through survey monkey online, Facebook and Whatsapp. Data analysis was conducted with the help of SPSS AMOS and Structural Equation Modeling with the aid of Path Diagrams. The study confirmed that both augmented reality marketing and price have a significant impact on brand image and purchase intention. In addition, it was also proven that there are positive interaction effects between brand image on both augmented reality marketing and perceived price towards customer purchase intention. The study found that augmented reality marketing does have a significant impact on brand image and consumer purchasing intention. The correlations analysis indicates that embedding augmented reality technology in Shopee's mobile application would improve customer's enjoyment, feeling and motivation towards Shopee, which subsequently form a greater level of cognitive thinking, affection and activation on the brand. The outcome of the study was similar to previous studies - however what was new from the study was the study took on a case study approach using a popular online store like Shopee to study the impact of augmented reality marketing and the confirmation of augmented reality does have a significant impact on purchase intention.